Analytical and numerical evaluation of configuration factors in radiation heat transfer. - Gupta, Kamlesh Gopal. (University of Ottawa (Canada), 1969)
The object of this thesis is twofold; on the one hand the radiation configuration factors for certain fundamental geometries---not previously treated in the literature---have been developed and, on the other hand, an entirely new approach proposed by Feingold* has been investigated, leading to a series of new analytical formulas involving spheres and infinitely long cylinders. Particularly significant are two hitherto unobserved conclusions; namely that the radius of the radiating sphere or of infinitely long cylinder does not affect the factor from that body to an entire class of surfaces described in the thesis, and that the Lambertian postulate of non-preferential distribution of radiation intensity over the surfaces of spheres and infinitely long cylinders is not necessary to the calculation of factors from these bodies. Several graphs have been plotted which should form a useful addition to the collection of similar data already available in the standard textbooks.
Keywords: Engineering, Mechanical.